Sustainable development of supplier performance. An empirical analysis of relationship characteristics in the automotive sector - Jule Naffin; Johanna Klewitz; Stefan Schaltegger (Corporate Social Responsibility and Environmental Management, 2023)
Sustainability performance of suppliers has become increasingly important for both corporate practice and research. While the importance of relationships between the focal company and its suppliers has been acknowledged for improving sustainability performance of suppliers, little is known about the role of relation specific factors in practice. This research fills this gap by empirically analyzing the relevance of relationspecific factors for the sustainability performance of suppliers based on a unique data set of 736 first-tier suppliers of a German original equipment manufacturer in the automotive industry. The analysis reveals that the sustainability performance of suppliers relates positively to transaction volume and relationship length as specific forms of relation specific characteristics as well as strategic partnership as a proxy of incentivized, in-depth cooperation and knowledge exchange. Each of the investigated relation-specific characteristics show a link with either environmental or with social performance. Conclusions are drawn for research and management.
Keywords: 650; automotive sector; relational-view; relation-specific factors; suppliers; sustainability performance